Peningkatan Aktifitas dan Hasil Belajar Siswa pada Mata Pelajaran Kesehatan, Keselamatan Kerja (K3) dan Higiene Sanitasi dengan Menggunakan Media Power Point - Yunizar Yunizar (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2022)
The background of this study was low activity and student learning outcomes in subjects Health, Safety (K3) and Sanitation Hygiene at SMK Negeri 2 Depok. The purpose of research is to improve the activity and student learning outcomes in subjects K3 and Sanitation Hygiene using media power point. This type of research is classroom action research conducted with three cycles. The study consists of four stages, namely planning, action, observation, and reflection. The low yield obtained learners learn the mastery of learning materials due to various factors. Low learning outcomes are influenced by two factors, namely internal and external factors